Musical Adaptations of Plautus’ Amphitryon on Broadway and in Türkiye - Sitare Bilge (Konservatoryum)
This study deals with the origin and definition of musical theater as a discipline throughout history and investigates A Funny Thing Happened on the Way to the Forum (Shevelove & Gelbart, 1962) based on Plautus’ play Amphitryon, as well as the Turkish play Amphitryon 2000 (Dormen, 2000) in terms of musical farce as a sub-genre of musical theater from the perspective of the stage director. In this sense, the study uses these musical theater plays to form a joint identity in terms of their musical pieces, as well as the dramaturgy of the texts. In this way, the study provides a roadmap for stage directors and scholars using academic and scientific methods consisting of a detailed literature review over a conceptual and theoretical framework, period research, and an examination of the above-mentioned works considering the connections between them based on the collected data. As a result, this article presents the impact of American musicals on Turkish musical plays by showing the similarities and differences between them through the valuable contributions of the writer and director Haldun Dormen